Analysis of Emotional Intelligence and Learning Outcomes of Students in Science Learning - Gunawan Gunawan; Agus Ramdani; Saprizal Hadisaputra (Jurnal Penelitian Pendidikan IPA, 2022)
Emotional intelligence is one indicator of academic success, where students who have high emotional intelligence will be active and work better in their groups. Emotional intelligence is very necessary for understanding the lesson delivered by the teacher. This study aims to analyze the effect of the learning model on student learning outcomes and analyze the influence of emotional intelligence on student learning outcomes. This study uses 3 learning models, namely, Project-Based Learning (PBL), guided inquiry, and conventional. This study employs a quasi-experimental method known as "factorial design 3 x 3. Data was collected using a questionnaire sheet to measure the emotional intelligence of students and an essay test to measure student learning outcomes. Data analysis used normality test, homogeneity test, and hypothesis test using one-way ANOVA at a significant level of 0.05. The results of testing the learning model hypothesis using analysis of variance (ANOVA) with the SPSS version 22 for windows program at a significant level, = 0.05, obtained a significance value (0.003 <0.05). This shows that there is an influence of learning models and emotional intelligence on student learning outcomes. The results of testing the emotional intelligence hypothesis at a significant level, = 0.05, obtained a significance value (0.001>0.05). This shows that there is an influence of emotional intelligence on student learning outcomes